TANGGUNG JAWAB DIREKSI PT. RIAU AIRLINES TERHADAP PARA PEMEGANG SAHAM SETELAH GAGAL USAHA - Lubis, Erick Rianto F.; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Board of Directors shall be fully responsible for the management and operation of the Company for the company's purposes and objectives. In carrying out its duties, the directors are granted full rights and powers, with the consequence that any actions and acts committed by the board of directors shall be deemed and treated as actions and actions of the company, as long as they act in accordance with those specified in the articles of association of the company. As long as the board of directors does not violate the articles of association of the company, the company shall bear all the consequences of the actions of the Board of Directors, while for the actions of the Board of Directors that harms the Company, which it does outside the limits and authority granted to it by the articles of association, . This means that the board of directors is personally liable for his actions beyond the limits of authority granted in the company's articles of association. Based on this understanding, the writing of this thesis formulates two formulation of the problem. Ie; First, the responsibility of the RAL board of directors to the Shareholders after the Second attempt fails, the efforts that must be made by the Board of Directors in executing the responsibilities to the Shareholders after the unsuccessful attempt.This type of research can be classified in the type of research This legal research is a normative juridical research, namely: research that discusses the legal aspect, by conducting library research in terms of comparative law or legal history oriented to the legislation Shall apply, inter alia: Law Number 1 Year 1995 Concerning Limited Liability Company, Law Number 40 Year 2007 About Limited Liability Company. The authors in this paper focus more on aspects of law that are closely related to the responsibility of the Board of Directors to the Shareholders.From the results of research problems there are two main things that can be concluded First, Responsibility is the obligation of an individual individual to carry out activities assigned to him as possible, according to his ability. The responsibilities of the Board of Directors are regulated in Law Number 40 Year 2007 regarding Limited Liability Company, namely the Board of Directors is responsible for the management of the Company as referred to in Article 92 paragraph.Second, the efforts of the board of directors of a Limited Liability Company (PT), are based on the principle that each member of the Board of Directors is personally liable for the loss of the Company if the person is guilty or negligent in performing his duties. If the Board of Directors consists of 2 (two) members of the Board of Directors or more, the responsibilities as referred to, apply jointly to each member of the Board of Directors.. Shareholders after the failure of the business as stipulated in Law Number 40 Year 2007 regarding Limited Liability Company has been lacking in giving a sense of justice and legal certainty for the shareholders. Keywords: Responsibility - Limited Liability Company - Business Failure – Shareholder